Serum Aminotransferases Levels in Obese and Normal Individuals in Tertiary Care Centre: A Case-Control Study - Sanketh, Dr. S. J.; Herakall, Dr. M.G.; Poojari, Dr. Mahesh (International Research in Medical and Health Sciences, 2025)
Background and Objectives: Obesity represents a significant global health challenge with potential metabolic complications. This case-control study aimed to comparatively evaluate serum aminotransferase levels in obese and normal-weight individuals to understand the relationship between obesity and hepatic enzyme alterations. Methods: A Case-Control study was conducted in a tertiary care centre involving 100 participants (50 obese and 50 normal-weight controls), aged 20-60 years. Participants were classified based on Body Mass Index (BMI). Serum levels of Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST), and Alkaline Phosphatase (ALP) were measured using standardized biochemical techniques. Demographic data, anthropometric measurements, and enzyme levels were systematically recorded and statistically analyzed. Results: Significant differences were observed in serum aminotransferase levels between obese and normal-weight groups. Mean ALT levels were 62.4 ± 22.7 U/L in obese participants compared to 35.2 ± 8.9 U/L in controls (p<0.001). Similarly, AST levels were 54.6 ± 18.3 U/L in obese individuals versus 32.7 ± 6.5 U/L in normal-weight participants (p<0.001). The prevalence of elevated enzyme levels was substantially higher in the obese group: 38% for ALT >50 U/L, 32% for AST >40 U/L, and 28% for ALP >75 U/L. Odds ratios demonstrated a significantly increased risk of enzyme elevation in obese participants (ALT OR 7.42, 95% CI 2.31-23.85). Conclusion: The study reveals a significant association between obesity and elevated serum aminotransferase levels, suggesting potential hepatic metabolic alterations in obese individuals. These findings underscore the importance of comprehensive metabolic monitoring and early interventions in obesity management.